Glucose-Dependent Insulinotropic Polypeptide and Substance P Mediate Emetic Response Induction by Masked Trichothecene Deoxynivalenol-3-Glucoside through Ca2+ Signaling - Qin, Zihui; Zhang, Hua; Wu, Qinghua; Wei, Ben; Wu, Ran; Guo, Xinyi; Xiao, Huiping; Wu, Wenda (Toxins, 2022)
Deoxynivalenol (DON), the most naturally-occurring trichothecenes, may affect animal and human health by causing vomiting as a hallmark of food poisoning. Deoxynivalenol-3-glucoside (D3G) usually co-occurs with DON as its glucosylated form and is another emerging food safety issue in recent years. However, the toxicity of D3G is not fully understood compared to DON, especially in emetic potency. The goals of this research were to (1) compare emetic effects to D3G by oral and intraperitoneal (IP) routes and relate emetic effects to brain-gut peptides glucose-dependent insulinotropic polypeptide (GIP) and substance P (SP) in mink; (2) determine the roles of calcium-sensing receptor (CaSR) and transient receptor potential (TRP) channel in D3G's emetic effect. Both oral and IP exposure to D3G elicited marked emetic events. This emetic response corresponded to an elevation of GIP and SP. Blocking the GIP receptor (GIPR) diminished emetic response induction by GIP and D3G. The neurokinin 1 receptor (NK-1R) inhibitor Emend® restrained the induction of emesis by SP and D3G. Importantly, CaSR antagonist NPS-2143 or TRP channel antagonist ruthenium red dose-dependently inhibited both D3G-induced emesis and brain-gut peptides GIP and SP release; cotreatment with both antagonists additively suppressed both emetic and brain-gut peptide responses to D3G. To summarize, our findings demonstrate that activation of CaSR and TRP channels contributes to D3G-induced emesis by mediating brain-gut peptide exocytosis in mink.
Keywords: glukosa; glukosidy; Glucosides; receptory gastrointestinálních hormonů; Mink; Receptors, G-Protein-Coupled; Vomiting; trichotheceny; calcium-sensing receptor; Trichothecenes; emesis; zvracení; receptory spřažené s G-proteiny; zvířata; brain-gut peptide; Receptors, Gastrointestinal Hormone; Emetics; emetika; deoxynivalenol-3-glucoside; norek; substance P; Substance P; transient receptor potential channel; Glucose; Animals